2004
DOI: 10.1111/j.1468-3083.2004.00970.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous tuberculosis in Indian children: the importance of screening for involvement of internal organs

Abstract: Cutaneous tuberculosis in children continues to be an important cause of morbidity, there is a high likelihood of internal involvement, especially in patients with scrofuloderma. A search is required for more sensitive, economic diagnostic tools. Response to treatment at 4 weeks often helps in substantiating the diagnosis of tuberculosis in doubtful cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
107
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(122 citation statements)
references
References 15 publications
12
107
1
1
Order By: Relevance
“…1 The prevalence among various dermatology outpatient departments in India ranges between 0.1% and 0.5% due to increase in prevalence of HIV and other immunocompromised state. 2,3 The risk factors of acquiring cutaneous tuberculosis increases with HIV infection, intravenous drug abuse, diabetes mellitus, immunosuppressive therapy, malignancies, end-stage renal disease and infancy.…”
Section: Discussionmentioning
confidence: 99%
“…1 The prevalence among various dermatology outpatient departments in India ranges between 0.1% and 0.5% due to increase in prevalence of HIV and other immunocompromised state. 2,3 The risk factors of acquiring cutaneous tuberculosis increases with HIV infection, intravenous drug abuse, diabetes mellitus, immunosuppressive therapy, malignancies, end-stage renal disease and infancy.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Severe reactions resulting in vesiculation or ulceration have also been observed in children. [1], [3] Tuberculin test is more commonly positive in tuberculids, as reported in all cases of LS by Singal et al [4] The role of BCG as a preventive measure against cutaneous TB is difficult to define. Protective efficacy of BCG vaccine in TB in various clinical trials has ranged from 0% to 80%.…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…Pandhi et al reported 66 of 68 children (97.1%) with positive Mantoux test with induration ranging from 10 to 32 mm. [1] Kumar et al observed that of their children with cutaneous TB, 91.8% patients with localised disease had positive Mantoux test as against only 50% of the cases with disseminated disease. [2] Severe reactions resulting in vesiculation or ulceration have also been observed in children.…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…Para el mismo año, según reportes del Ministerio de Salud de Chile, la prevalencia de tuberculosis en el país era de 13,8 por 100.000 habitantes 2 . La tuberculosis cutánea es una forma poco común dentro de las presentaciones extrapulmonares, con una prevalencia cercana a 1,5%, entre todos los casos de tuberculosis extrapulmonar 3,4,5 . El agente etiológico es principalmente Mycobacterium tuberculosis, pero en algunos casos se encuentra Mycobacterium bovis, y menos frecuentemente el bacilo de Calmette-Guérin (BCG) 6 .…”
Section: Introductionunclassified